"استخدام نماذج GARCHللتنبؤ بتقلبات أسعار الواردات دراسة حالة -الصين- خلال الفترة 2000 إلى 2019 " - بن علي, ايوب; صهيب, بن خليفة; حسام الدين, شنوف (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى نمذجه تقلبات أسعار الوردات الصينية خلال فترة زمنية من خلال 2000 على 2019 وذالك بإستخدام بيانات شهرية تمتد من 31\09\2019 بحيث تم الإعتماد على متغير وحيدة تتمثل في عوائد تقلبات أسعار الوردات وذالك بواقع عدد المشاهدات (238) ويتمثل مكان الدراسة في جمهورية الصين الشعبية . حيث قمنا بدراسة سلوك تقلبات عوائد أسعار الوردات بإعتماد على نموذج الانحدار المشروط بعدم ثبات التباين المعمم (GARCH) . حيث توصلنا من خلال هذه الدراسة إلى أنه يمكن لنموذج الانحدار الذاتي المشروط بعدم ثبات التباين المعمم أن يفسر سلوك عوائد تقلبات أسعار الوردات الصينية . ""This study aims to model the fluctuations in the prices of Chinese imports during a period of time through 2000 to 2019, using monthly data extending from 01/09/2019 so that the dependence on a single variable is represented in the returns of fluctuations in the prices of imports, according to the number of observations (238 ) and the place of study in the Republic People's Republic of China. We studied the behavior of fluctuations in the price of returns on the basis of the conditional regression model of generalized inconsistency inequality (GARCH). Where we have found through this study that the growth of c, the conditional regression of the generalized inconsistency variation can explain the behavior of the returns of fluctuations in Chinese import prices. "
مذكرة مالية وتجارة دولية
Keywords: عوائد – تقلبات – نموذج –إرتباط شرطي – ورادات – أسعار .; Returns - fluctuations - pattern - conditional engagement - imports - prices.